Ketersediaan Data dalam Mendukung Smart City Readiness di Kota Surakarta - Miraeki Herawati; Achmad Djunaedi (P4W LPPM IPB, 2020)
Data Availability in Supporting Smart City Readiness in Surakarta City The smart city concept is one of the developing concepts in overcoming various urban problems. The concept must be supported by mature implementation guidelines. The preparation of smart city guidelines is based on the readiness of each region. The readiness measurement is carried out with smart city readiness measurements that have been developed by several experts. This study will use compilation of several smart city readiness measurement models to measure smart city readiness in Surakarta City, in order to understand data required and available in Surakarta City Government, data required and available outside Surakarta City Government, and data required but not yet provided by both the City Government and other agencies. The method used in this study is case study with a qualitative approach. Measurement results show that the availability of data and the quality of available data in Surakarta City is quite good. This shows that Surakarta City is ready to develop the smart city concept to overcome various city problems faced.